PENGARUH KOMITMEN PEMILIK DAN DUKUNGAN PEMERINTAH TERHADAP PENGGUNAAN SISTEM INFORMASI AKUNTANSI - fauziah, maulina (Pascasarjana Universitas Sultan Ageng Tirtayas, 2021)
The purpose of this study is to examine the effect of owner’s commitment and government support on the use of accounting information systems at SMEs sub-district of Tampan in Pekanbaru. The Data analysis methods used is descriptive analysis and hypothesis test. The data used in this study are primary data with questionnaires as an instruments. The population in this study are SMEs engaged in industry of Tampan sub-district in Pekanbaru. This study uses the Slovin Method as a measuring tool to calculate the sample size. The method of sampling used is stratified random sampling method. Respondents in this study are owner of SMEs in industrial sector of Tampan sub-district in Pekanbaru which amounts 93 units. So the total number of questionnaires distributed was 93. The results of this study indicate that owner’s commitment and government support have a positive effect on the use of accounting information systems. The results showed that the high commitment of the owner and the availability of government support can increase the use of accounting information systems in SMEs. In the digital era, accounting information systems can be accessed easily with available applications, SMEs owner should increase their commitment and take advantage of the support provided by the government.